The Comprehension Theories Of Continuous Intention To Use Tel With E-Learning Models In Educations - Tawafak, Ragad M.; Awanis, Romli; Ruzaini, Abdullah Arshah; Aziman, Abdullah (2019)
This study analyses comprehensive of the existing theories that validate the accuracy of technology acceptance models (TAM). Also, examining the adopted TAM factors in conjunction with massive open online course (MOOC) features for continuous intention to use. The main problem phased TAM is the adoption of the right factors used for modelling design. The objective is to come out with the common factors could be used in e-learning. The method of this study is based on the combination between the application of technology-enhanced learning (TEL) techniques factors and the facilities of e-learning factors. This combination can be tested by adopted model as it provides flexibility to both lecturers and students. The finding shows the variety additional factors used as of academic performance, and TAM factors with continuous intention to use e-learning are significant positive values for e-learning in educations.